PANDANGAN ISLAM DAN PERSEPSI MASYARAKAT TERHADAP TRADISI BUNGUNG BARANIA DI KUTULU KELURAHAN MATAALLO KECAMATAN BAJENG KABUPATEN GOWA - Audah Mannan; Ira Wardani Aqsa (Jurnal Komodifikasi, 2019)
This study aims to determine the stages of the implementation of the Bungung Barania tradition in Kutulu, to determine people's perceptions of the Bungung Barania tradition in Kutulu and to determine the Islamic view of the Bungung Barania tradition in Kutulu. This type of research is a qualitative descriptive research that is directly by getting information from informants such as circumstances, processes, events / events expressed in the form of words. By using a phenomenological approach, the aim is to describe the paradigm or perspective of reality. Data obtained by observing, interviewing, and documenting. The results showed that the stages of the implementation of the Bungung Barania tradition were talking to the teacher, the time for prayer climbing, the bathing process, the meaning of the Bungung Barania tradition, namely tradition originating from ancestors, a form of gratitude to Allah, the Islamic view of the Bungung Barania tradition was polytheists. The implication of the research shows that the Bungung Barania tradition cannot be separated from the lives of the people of Kutulu even though they are religious communities as a result they become a syncretism society, namely a society that combines religious beliefs with cultural beliefs. As a result, syncretism can not be avoided from the habits of the people of Kutulu, in connection with this religious leaders, villages, youth, need to do socialization related to this cultural belief that tends to be outside of Islamic religious rituals (polytheists or haram).